The Use of Differentiated Instruction with Technological Support for Teaching English in Primary School - Hanif Maulaniam Sholah; Bambang Yudi Cahyono; Suhono, Suhono (Scidac Plus, 2025)
In the era of personalized learning, Differentiated Instruction (DI) has emerged as a pedagogical approach that accommodates the diverse needs, readiness, and learning preferences of students. However, available research about the practice of DI, especially when integrated with technology in English language teaching, remains limited, leaving its practical implementation unclear. This study aims to investigate the use of DI supported by technology in teaching English in Indonesian primary schools. Employing a qualitative case study design across three school settings, data were collected through classroom observations, document reviews, and in-depth interviews with English teachers and headmasters. Thematic analysis was used to explore DI strategies, the supporting factors, and the challenges in implementing DI. Findings revealed that DI was applied in stages, starting from initial assessments, grouping students based on learning readiness, and delivering tiered materials using various digital tools such as Kahoot, Duolingo, and Padlet. The implementation was supported by school leadership, national curriculum mandates, and teacher collaboration, but hindered by time constraints, preparation complexity, and potential perceptions of unfairness. This study provides practical insights and a model for applying DI in primary EFL classrooms using technological tools to enhance inclusive and student-centered instruction.